2017
DOI: 10.1155/2017/7698510
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Role in Providing Nutrition Advice during Pregnancy: Meeting the Challenges? A Qualitative Study

Abstract: This study explored the Australian midwives' role in the provision of nutrition advice. Little is known about their perceptions of this role, the influence of the model of care, and the barriers and facilitators that may influence them providing quality nutrition advice to pregnant women. Semistructured telephone interviews were undertaken with a subsample (n = 16) of the members of the Australian College of Midwives who participated in an online survey about midwives' nutrition knowledge, attitudes, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 21 publications
3
78
0
2
Order By: Relevance
“…It is important that the PHNs also derived positive and successful experiences from the counseling process as the need for counseling is increasing along with the growing number of women diagnosed with GDM 19 . These results are similar to the existing literature describing the lack of training for health professionals related to nutrition [26][27][28][29][30][31] . An inconsistency, between different nutrition and PA guidelines related to the suggested type of physical activity and the content of diet recommendations, was raised and also the pregnant women's view that the counseling was both contradictory and confusing 21,[32][33][34] .…”
Section: Discussionsupporting
confidence: 90%
“…It is important that the PHNs also derived positive and successful experiences from the counseling process as the need for counseling is increasing along with the growing number of women diagnosed with GDM 19 . These results are similar to the existing literature describing the lack of training for health professionals related to nutrition [26][27][28][29][30][31] . An inconsistency, between different nutrition and PA guidelines related to the suggested type of physical activity and the content of diet recommendations, was raised and also the pregnant women's view that the counseling was both contradictory and confusing 21,[32][33][34] .…”
Section: Discussionsupporting
confidence: 90%
“…In the United Kingdom, satisfaction with pregnancy services is reportedly high (Henderson & Redshaw, ). In Australia, midwives were described as being in a position of trust with the women in their care, making them ideally placed to deliver a brief intervention (Arrish et al, ). These Australian midwives struggled however to find time within the existing care pathway to have effective conversations about nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic brief interventions delivered as part of routine primary care appointments have been shown to achieve significant improvements in health behaviours, including weight loss and smoking reduction, particularly if delivered by respected and trusted authorities (Aveyard et al, ; Aveyard, Begh, Parsons, & West, ). Consequently, there have been calls for midwives to use the relationship of trust they have with pregnant women in their care to engage women in improving their diets and nutritional status (Arrish, Yeatman, & Williamson, ). In the United Kingdom, these calls come in the context of Public Health England's agenda for “making every contact count” (NHS Health Education England, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study at Gote Geda Woreda, East Wollega Zone, Ethiopia showed that the information on nutrition had a significant relationship with the knowledge of pregnant mothers about nutrition .That study showed women who had information about nutrition were 3.6 times more likely knowledgeable about nutrition as compared to the pregnant women with no information about nutrition during pregnancy (AOR=3.59) (Fekadu Beyene, 2013).The adequacy of protein, vitamin C, and iron in the daily diet of pregnant mothers needs to be considered because it has a role to prevent anemia (Abdelwahid, 2013;Brown & Shapiro, 1996;Rivera-rodriguez, Rodríguez-rivera, Roman-julia, & Raul, 2016;Sriramanakoppa, Sreenivas, & Jayaram, 2015). Pregnant mothers need to be givena health education about foods that contain of protein, vitamin C, and iron during antenatal care.Midwivesplayan important role to improve the understanding ofpregnant mothers (Arrish, Yeatman, & Williamson, 2017).…”
Section: Introductionmentioning
confidence: 99%